A composite structure electrode and its preparation method and application
During the preparation process of composite structure electrodes, it was divided into two low-temperature isostatic pressure treatments, which solved the interfacial reaction between the oxide electrolyte and the positive electrode active material during high-temperature sintering and the crystal structure phase transformation of the positive electrode active material, which significantly improved the electrochemical performance of the electrode.
Patent Information
- Application Number
- CN202210638785.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-06-07
AI Technical Summary
In the prior art, the oxide electrolyte and the positive electrode active material are prone to interfacial reactions during high temperature sintering, and the positive electrode active material undergoes crystal structure phase transformation during secondary sintering at high temperature, resulting in deterioration of the electrode electrochemical performance.
By using the preparation method of composite structure electrodes, the primary isostatic pressure treatment and secondary isostatic pressure treatment at a temperature not higher than 600°C, high-temperature sintering is avoided, the interface reaction between the oxide electrolyte and the positive electrode active material is reduced, and the crystal structure phase transformation of the positive electrode active material is prevented.
The interface reaction between the oxide electrolyte and the positive electrode active material and the crystal structure phase transformation of the positive electrode active material are effectively avoided, which significantly improves the electrochemical performance of the electrode and reduces the porosity and internal interface resistance.
Smart Images

Figure CN115117296B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electric vehicle power batteries, and in particular to a composite structure electrode and a preparation method and application thereof. Background Art
[0002] Oxide solid electrolyte materials are currently the most promising type of solid electrolyte materials for industrial applications due to their advantages such as high room temperature conductivity and stable chemical properties in the air. In the process of preparing electrodes, solid electrolyte materials need to be mixed with positive electrode active materials. However, their compatibility with positive electrode active materials is poor. In order to reduce the porosity of solid electrolytes and improve conductivity, the sintering temperature of raw materials during the preparation process usually needs to reach above 1000°C. However, the currently commonly used positive electrode active materials will react with electrolyte materials at the interface at around 700°C, thus affecting the electrode performance.
[0003] The existing technology is to physically isolate the interface by coating the surface of the positive electrode active material before sintering. However, even so, the commonly used positive electrode active materials will undergo crystal structure phase transformation when the temperature exceeds 700-800°C, resulting in serious deterioration of the electrochemical performance of the electrode.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The present invention provides a composite structure electrode and a preparation method and application thereof, so as to solve the problems in the prior art of reaction between the oxide electrolyte and the positive electrode active material interface during high-temperature sintering exceeding 700°C, and phase transformation of the crystal structure of the positive electrode active material during secondary sintering at high temperature (exceeding 700°C).
[0006] In order to solve the above problems, the first aspect of the present invention provides a composite structure electrode, wherein the electrode is prepared by using a current collector, a positive electrode active material, a solid electrolyte material, a conductive agent and an auxiliary agent as raw materials, and is subjected to an isostatic pressing treatment at a temperature not higher than 600°C, and then coated with the solid electrolyte material and the auxiliary agent, and is subjected to a secondary isostatic pressing treatment at a temperature not higher than 600°C in an environment with an auxiliary organic solvent, to obtain the electrode. This solution reasonably divides the high-temperature sintering (above 700°C) in the prior art into two low-temperature sinterings (below 600°C). During the entire preparation process, the sintering temperature is always controlled below 600°C, thereby effectively avoiding the interface reaction between the oxide electrolyte and the positive electrode active material, and avoiding the phenomenon of crystal structure phase transformation during the secondary sintering of the positive electrode active material under high temperature conditions (above 700°C).
[0007] In other preferred embodiments, the temperature of the first isostatic pressing treatment is 300° C. to 500° C., and the temperature of the second isostatic pressing treatment is 400° C. to 600° C. The temperatures of the two isostatic pressing treatments are both below 700° C., which can avoid interface reactions between the oxide electrolyte and the positive electrode active material.
[0008] A second aspect of the present invention provides a method for preparing the composite structure electrode, comprising the following steps:
[0009] a. A positive electrode active material, a solid electrolyte material, a conductive agent and an auxiliary agent are used as raw materials for preparation, and mixed to form a first slurry, the first slurry is coated on the surface of the current collector, and an isostatic pressing treatment is performed at a temperature not higher than 600° C. to obtain a pole piece A;
[0010] b. Mixing the solid electrolyte material and the auxiliary agent to obtain a second slurry, and applying it on the surface of the pole piece A, and obtaining the pole piece B after drying;
[0011] c. After the electrode piece B is contacted with an auxiliary organic solvent, a secondary isostatic pressing treatment is performed at a temperature not higher than 600° C. to obtain the electrode.
[0012] In other preferred embodiments, the auxiliary agent is a mixture of a flux, a binder and a solvent.
[0013] In other preferred embodiments, the solid electrolyte material is at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium lanthanum zirconium tantalum oxide, and lithium aluminum titanium phosphate.
[0014] In other preferred embodiments, the auxiliary organic solvent is at least one of ethers, hydrocarbons, esters, ketones, tetrahydrofuran, dioxolane and acetonitrile, which can play a lubricating role in the preparation process.
[0015] In other preferred embodiments, in step a, the mass ratio of the positive electrode active material, the solid electrolyte material, the flux, the binder and the conductive agent is (55-65): (35-45): (5-10): 5:3.
[0016] In other preferred embodiments, in step b, the mass ratio of the solid electrolyte material, the flux and the binder is (90-110):(5-10):5.
[0017] In other preferred embodiments, the positive electrode active material is NCM811, and the solid electrolyte material is LLZO.
[0018] In other preferred embodiments, both the primary isostatic pressing treatment and the secondary isostatic pressing treatment need to meet the following requirements: the pressure is 10 to 800 MPa, the single pressure holding time is 10 to 600 min, and the number of pressurization times is 1 to 10 times.
[0019] The third aspect of the present invention provides an application of the composite structure electrode in an all-solid-state battery.
[0020] The composite structure electrode provided in the present application first prepares a first slurry, and applies it on the surface of the current collector, and performs an isostatic pressing treatment at a temperature not higher than 600°C to obtain a pole piece A; then prepares a second slurry, and applies it on the surface of the pole piece A, and obtains a pole piece B after drying; finally, the pole piece B is contacted with an auxiliary organic solvent, and a secondary isostatic pressing treatment is performed at a temperature not higher than 600°C to obtain a composite structure electrode. The entire preparation process is carried out under a temperature environment of 300 to 600°C, so that the interface reaction between the oxide electrolyte and the positive electrode active material can be effectively avoided, and the crystal structure phase transformation phenomenon of the positive electrode active material during the secondary sintering under high temperature conditions can be avoided. And it has been experimentally proved that the electrode prepared by the method recorded in this scheme has a significantly lower porosity, a significantly lower interface internal resistance, and a significantly improved electrochemical performance compared with ordinary electrodes, and has a good promotion prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A schematic diagram of a process for preparing a specific composite structure electrode provided in this application;
[0023] Figure 2 is a porosity diagram of different electrodes in this application;
[0024] Figure 3 It is the AC impedance diagram of different electrodes in this application;
[0025] Figure 4 This is a diagram of the first charge and discharge specific capacity of different electrodes in this application. DETAILED DESCRIPTION
[0026] In order to make the above and other features and advantages of the present invention more clear, the present invention is further described below in conjunction with the accompanying drawings. It should be understood that the specific embodiments given herein are for the purpose of explaining to those skilled in the art and are only exemplary and not restrictive.
[0027] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0028] The present invention provides a composite structure electrode, which uses a current collector, a positive electrode active material, a solid electrolyte material, a conductive agent and an auxiliary agent as raw materials for preparation, performs an isostatic pressing treatment at a temperature not higher than 600°C, and then coats the solid electrolyte material and the auxiliary agent, and performs a second isostatic pressing treatment at a temperature not higher than 600°C in the presence of an auxiliary organic solvent to obtain the composite structure electrode.
[0029] In other embodiments, the composite structure electrode can be used to prepare an all-solid-state battery.
[0030] like Figure 1 On the other hand, the present invention also provides a method for preparing the composite structure electrode, comprising the following steps:
[0031] a. A positive electrode active material, a solid electrolyte material, a conductive agent and an auxiliary agent are used as raw materials for preparation, and mixed to form a first slurry, the first slurry is coated on the surface of the current collector, and an isostatic pressing treatment is performed at a temperature not higher than 600° C. to obtain a pole piece A;
[0032] b. Mixing the solid electrolyte material and the auxiliary agent to obtain a second slurry, and applying it on the surface of the electrode A, and obtaining the electrode B after drying;
[0033] c. After the electrode piece B is contacted with the auxiliary organic solvent, a secondary isostatic pressing treatment is performed at a temperature not higher than 600° C. to obtain an electrode.
[0034] The embodiment shows a specific method for preparing a composite structure electrode, which includes the following steps:
[0035] a. Prepare a composite positive electrode sheet and perform isostatic pressing treatment on it at 300-600°C;
[0036] b. preparing a solid electrolyte slurry and coating it on the surface of the electrode after treatment in step a;
[0037] c. The electrode treated in step b is fully contacted with an auxiliary organic solvent and subjected to isostatic pressing at 300-600°C.
[0038] In specific applications, this solution mainly includes three steps: a. Prepare a composite positive electrode plate and perform isostatic pressing at 300-600℃, and hot isostatic pressing can soften it; b. Prepare a solid electrolyte slurry and apply it on the surface of the plate treated in step a; c. Fully contact the plate treated in step b with an auxiliary organic solvent and perform isostatic pressing at 300-600℃, and the organic solvent can lubricate it. This solution splits the single sintering mechanism in the prior art into two sinterings. During the entire preparation process, the sintering temperature is always controlled at 300-600℃, so as to effectively avoid the reaction between the oxide electrolyte and the positive active material interface, and avoid the crystal structure phase transformation of the positive active material during the secondary sintering under high temperature conditions.
[0039] The invention is described below in conjunction with specific embodiments.
[0040] Example 1
[0041] a. coating the slurry on the surface of the current collector to prepare a composite positive electrode sheet, and performing an isostatic pressing treatment at 300 to 600°C;
[0042] In this embodiment, the current collector refers to a structure or part that collects current, and in lithium-ion batteries it mainly refers to metal foil, such as copper foil and aluminum foil. The slurry is a mixture of a positive electrode active material (such as NCM811, that is, a ternary lithium battery in which the positive electrode material is nickel, cobalt and manganese, and the content ratio is 80%:10%:10%), a solid electrolyte material, a flux, a binder, a conductive agent and a solvent. The mass ratio of the positive electrode active material, the solid electrolyte material, the flux, the binder and the conductive agent is (55-65): (35-45): (5-10): 5:3; the solid electrolyte material can be at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide, lithium lanthanum zirconium tantalum oxide, and lithium aluminum titanium phosphate. The flux, the binder, the conductive agent and the solvent are conventionally selected. The positive electrode active material can be lithium iron phosphate (LFP), lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, etc. The flux can be aluminum oxide, magnesium oxide, calcium oxide, silicon dioxide, etc. The binder can be polyvinylidene fluoride (PVDF), the conductive agent can be carbon black, conductive graphite, etc., and the solvent can be cyclic carbonate, ethylene carbonate (EC), etc.
[0043] b. preparing a solid electrolyte slurry and coating it on the surface of the electrode after treatment in step a;
[0044] The solid electrolyte slurry is a mixture of a solid electrolyte material, a flux, a binder, a conductive agent and a solvent, and the mass ratio of the solid electrolyte material, the flux and the binder in the solid electrolyte slurry is (90-110): (5-10): 5;
[0045] c. The electrode treated in step b is fully contacted with an auxiliary organic solvent and subjected to isostatic pressing at 300-600° C. The auxiliary organic solvent is at least one of ethers, hydrocarbons, esters, ketones, tetrahydrofuran, dioxolane and acetonitrile, which can play a lubricating role in the preparation process.
[0046] It should be noted that, in this embodiment and other embodiments, during each isostatic pressing process, the pressure is 10 to 800 MPa, the single pressure holding time is 10 to 600 min, and the number of pressurization times is 1 to 10 times.
[0047] Example 2
[0048] a. coating the slurry on the surface of the current collector to prepare a composite positive electrode sheet, and performing an isostatic pressing treatment at 300 to 600°C;
[0049] In this embodiment, the current collector adopts aluminum foil. The slurry is a mixture of positive electrode active material (such as NCM811, that is, a layered lithium oxide of nickel, cobalt and manganese in the positive electrode material, and the content ratio is 80%:10%:10% in a ternary lithium battery), lithium lanthanum titanium oxide, magnesium oxide, polyvinylidene fluoride, carbon black and ethylene carbonate (EC), and the mass ratio of positive electrode active material, lithium lanthanum titanium oxide, magnesium oxide, polyvinylidene fluoride and carbon black is 55:35:5:5:3; the solid electrolyte material can be at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide, lithium lanthanum zirconium tantalum oxide, and aluminum titanium lithium phosphate. The flux, adhesive, conductive agent and solvent are conventionally selected, and the flux can be aluminum oxide, magnesium oxide, calcium oxide, silicon dioxide, etc. The adhesive can be polyvinylidene fluoride (PVDF), the conductive agent is carbon black, conductive graphite, etc., and the solvent can be cyclic carbonate, ethylene carbonate (EC), etc. The selection of flux, adhesive, conductive agent and solvent can be adaptively adjusted, which is a conventional technical means in this field.
[0050] b. Prepare a solid electrolyte slurry and apply it on the surface of the electrode after being treated in step a; the mass ratio of the solid electrolyte material, flux and adhesive in the solid electrolyte slurry is 90:5:5, and the solid electrolyte material, flux and adhesive in step b can adopt the components in step a.
[0051] c. The electrode treated in step b is fully contacted with an auxiliary organic solvent and subjected to isostatic pressing at 300-600° C. The auxiliary organic solvent is at least one of ethers, hydrocarbons, esters, ketones, tetrahydrofuran, dioxolane and acetonitrile, which can play a lubricating role in the preparation process.
[0052] The other conditions of this embodiment are the same as those of Embodiment 1 and will not be described in detail here.
[0053] Example 3
[0054] a. coating the slurry on the surface of the current collector to prepare a composite positive electrode sheet, and isostatically pressing the same at 400°C for 6h;
[0055] In this embodiment, the mass ratio of the positive electrode active material, the solid electrolyte material, the flux, the binder and the conductive agent is 65:45:10:5:3.
[0056] In this embodiment, the current collector adopts aluminum foil. The slurry is a mixture of positive electrode active material (such as NCM811, that is, the positive electrode material is nickel, cobalt and manganese, and the content ratio is 80%:10%:10%), lithium lanthanum titanate, lithium manganate, polyvinylidene fluoride, carbon black and ethylene carbonate (EC), and the mass ratio of positive electrode active material, lithium lanthanum titanate, lithium manganate, polyvinylidene fluoride and carbon black is 65:45:10:5:3; the solid electrolyte material can be at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanate, lithium lanthanum zirconium tantalum oxide, and lithium aluminum titanium phosphate. The flux, adhesive, conductive agent and solvent are conventionally selected, and the flux can be aluminum oxide, magnesium oxide, calcium oxide, silicon dioxide, etc. The adhesive can be polyvinylidene fluoride (PVDF), the conductive agent is carbon black, conductive graphite, etc., and the solvent can be cyclic carbonate, ethylene carbonate (EC), etc. The selection of flux, adhesive, conductive agent and solvent can be adaptively adjusted, which is a conventional technical means in this field.
[0057] b. Prepare a solid electrolyte slurry and apply it on the surface of the electrode after being treated in step a; the mass ratio of the solid electrolyte material, flux and adhesive in the solid electrolyte slurry is 110:10:5.
[0058] c. The electrode treated in step b is fully contacted with an auxiliary organic solvent and subjected to isostatic pressing at 550°C. The specific processing process is: at 550°C, isostatic pressing is performed for 4 hours followed by a 15-minute break, and repeated 4 times to obtain a composite structure electrode.
[0059] The other conditions of this embodiment are the same as those of Embodiment 1 and will not be described in detail here.
[0060] Example 4
[0061] a. coating the slurry on the surface of the current collector to prepare a composite positive electrode sheet, and performing an isostatic pressing treatment at 300 to 600°C;
[0062] In this embodiment, the mass ratio of the positive electrode active material, the solid electrolyte material, the flux, the binder and the conductive agent is 60:40:10:5:3.
[0063] b. Prepare a solid electrolyte slurry and apply it on the surface of the electrode after being treated in step a; the mass ratio of the solid electrolyte material, flux and adhesive in the solid electrolyte slurry is 100:10:5.
[0064] c. The electrode treated in step b is fully contacted with an auxiliary organic solvent and subjected to isostatic pressing at 300-600°C.
[0065] The other conditions of this embodiment are the same as those of Embodiment 1 and will not be described in detail here.
[0066] Example 5
[0067] The method for preparing the composite structure electrode in this embodiment includes the following steps:
[0068] S1: NCM811, LLZO, LFP, PVDF, conductive graphite and cyclic carbonate are mixed to form slurry A (the mass ratio of NCM811, LLZO, LFP, PVDF and conductive graphite is 60:40:10:5:3), which is coated on the surface of the current collector, and then dried and isostatically pressed at 400°C to obtain a pole piece A;
[0069] S2: LLZO, LFP, PVDF and cyclic carbonate are mixed to form slurry B (the mass ratio of LLZO, LFP and PVDF in slurry B is 100:10:5), slurry B is coated on the surface of pole piece A, and pole piece B is obtained after drying;
[0070] S3: The electrode piece B is fully contacted with the auxiliary organic solvent, and then subjected to an isostatic pressing treatment at 550° C. to obtain a composite structure electrode.
[0071] The other conditions of this embodiment are the same as those of Embodiment 1 and will not be described in detail here.
[0072] Example 6
[0073] The method for preparing the composite structure electrode in this embodiment includes the following steps:
[0074] S1: NCM811, LLZO, LFP, PVDF, conductive graphite and cyclic carbonate are mixed to form slurry A (the mass ratio of NCM811, LLZO, LFP, PVDF and conductive graphite is 60:40:10:5:3), which is coated on the surface of the current collector, and then dried and isostatically pressed at 400°C to obtain a pole piece A;
[0075] S2: LLZO, LFP, PVDF and cyclic carbonate are mixed to form slurry B (the mass ratio of LLZO, LFP and PVDF in slurry B is 100:10:5), slurry B is coated on the surface of pole piece A, and pole piece B is obtained after drying;
[0076] S3: The electrode piece B is fully contacted with ether, and then subjected to isostatic pressing at 550° C. to obtain a composite structure electrode.
[0077] The other conditions of this embodiment are the same as those of Embodiment 1 and will not be described in detail here.
[0078] Example 7
[0079] The method for preparing the composite structure electrode in this embodiment includes the following steps:
[0080] S1: NCM811, LLZO, LFP, PVDF, conductive graphite and cyclic carbonate were mixed to form slurry A (the mass ratio of NCM811, LLZO, LFP, PVDF and conductive graphite was 60:40:10:5:3), coated on the surface of the current collector, dried, and isostatically pressed at 400°C for 6h to obtain the electrode A;
[0081] S2: LLZO, LFP, PVDF and cyclic carbonate are mixed to form slurry B, which is coated on the surface of pole piece A, and then dried to obtain pole piece B;
[0082] S3: The electrode piece B is fully contacted with ether, and then isostatically pressed. The specific operation is to perform isostatic pressing at 550°C for 4 hours, followed by a 15-minute break, and repeat this process 4 times to obtain a composite structure electrode.
[0083] Comparative Example 1 is to use conventional coating, drying, rolling and sintering of the electrode at 1000°C.
[0084] Comparative Example 2 is a positive electrode coated with lithium niobate and a coated, dried and rolled 1000°C electrode.
[0085] The porosity of the electrode sheets finally obtained in Example 7, Comparative Example 1 and Comparative Example 2 was measured using a mercury intrusion instrument and plotted on Figure 2 middle.
[0086] The AC impedance curves of the electrodes finally obtained in Example 7, Comparative Example 1 and Comparative Example 2 were measured using an electrochemical workstation and plotted on Figure 3 middle;
[0087] Button cells were made for electrochemical performance testing. The constant current charge and discharge cut-off voltage was 2.5-4.3 V, the charge and discharge current density was 20 mA / g (0.1 C), and the test temperature was 25 ° C. The first charge and discharge specific capacities of the electrodes finally prepared in Example 7, Comparative Example 1, and Comparative Example 2 were measured and plotted on Figure 4 middle.
[0088] analyze Figure 2-4 It can be seen that the electrode prepared by the method provided in this scheme has significantly reduced porosity and interfacial internal resistance, and significantly improved electrochemical performance compared with the electrode prepared by the conventional method. In addition, during the entire preparation process, the sintering temperature is always controlled below 700°C, thereby effectively avoiding the reaction at the interface between the oxide electrolyte and the positive electrode active material, and avoiding the crystal structure phase transition of the positive electrode active material during the secondary sintering under high temperature conditions, which has a very good promotion prospect.
[0089] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be construed as limiting the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that a person skilled in the art can think of. Specifically, the technical means of using solvent-assisted hot isostatic pressing is not limited to the preparation of oxide-based solid electrodes. For example, sulfide-based solid electrodes and halide-based solid electrodes also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a composite structure electrode, characterized in that: The electrode is prepared by using a current collector, a positive electrode active material, a solid electrolyte material, a conductive agent and an auxiliary agent as raw materials, performing an isostatic pressing treatment at a temperature not higher than 600° C., then coating the solid electrolyte material and the auxiliary agent, and performing a secondary isostatic pressing treatment at a temperature not higher than 600° C. in an environment with an auxiliary organic solvent, to obtain the electrode; The preparation method comprises the following steps: a. A positive electrode active material, a solid electrolyte material, a conductive agent and an auxiliary agent are used as raw materials for preparation, and mixed to form a first slurry, the first slurry is coated on the surface of the current collector, and an isostatic pressing treatment is performed at a temperature not higher than 600° C. to obtain a pole piece A; b. mixing the solid electrolyte material and the auxiliary agent to obtain a second slurry, and applying it on the surface of the pole piece A, and obtaining the pole piece B after drying; c. After the electrode piece B is contacted with an auxiliary organic solvent, a secondary isostatic pressing treatment is performed at a temperature not higher than 600° C. to obtain the electrode; Among them, the temperature of the first isostatic pressing treatment is 300°C to 500°C; the temperature of the second isostatic pressing treatment is 400°C to 600°C; the solid electrolyte material is at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium lanthanum zirconium tantalum oxide, and lithium aluminum titanium phosphate; the auxiliary agent is a mixture of flux, adhesive and solvent; the auxiliary organic solvent is at least one of ethers, hydrocarbons, esters, ketones, tetrahydrofuran, dioxolane and acetonitrile.
2. The method for preparing a composite structure electrode according to claim 1, characterized in that: In step a, the mass ratio of the positive electrode active material, the solid electrolyte material, the flux, the binder and the conductive agent is (55-65): (35-45): (5-10): 5:
3.
3. The method for preparing a composite structure electrode according to claim 2, characterized in that: In step b, the mass ratio of the solid electrolyte material, the flux and the binder is (90-110):(5-10):
5.
4. The method for preparing a composite structure electrode according to any one of claims 1 to 3, characterized in that: Both the primary isostatic pressing treatment and the secondary isostatic pressing treatment must meet the following requirements: the pressure is 10 to 800 MPa, the single pressure holding time is 10 to 600 minutes, and the number of pressurization times is 1 to 10 times.
5. A composite structure electrode as described in any one of claims 1 to 4 can be used in all-solid-state batteries.
Citation Information
Patent Citations
Cathode mixture, cathode, and all-solid-state lithium ion secondary battery, and method for manufacturing the same
CN107093764A